Civil liberties, national security and prospects for consensus : legal, philosophical, and religious perspectives - Reed, Esther D., 1965-; Dumper, Michael (Cambridge : Cambridge University Press, 2012)
'The idea of security has recently seen a surge of interest from political philosophers. After the atrocities of 11 September 2001 and 7 July 2005, many leading politicians justified encroachments on international legal standards and civil liberties in the name of security and with a view to protecting the rights of the people. Suggestions were made on both sides of the Atlantic to the effect that the extremism of terrorism required the security of the many to be weighed against the liberties of other citizens. In this collection of essays, Jeremy Waldron, Conor Gearty, Tariq Modood, David Novak, Abdelwahab El-Affendi and others debate how to move beyond the false dichotomy whereby fundamental human rights and international standards are conceived as something to be balanced against security. They also examine the claim that this aim might better be advanced by the inclusion in public debate of explicitly religious voices'--
Part I. The Security-Liberty Debate -- Safety and security / Jeremy Waldron -- Escaping Hobbes : liberty and security for our democratic (not anti-terrorist) age / Conor Gearty -- Moderate secularism, religion as identity and respect for religion / Tariq Modood -- Part II. Impact on Society : the Management of Unease -- From cartoons to crucifixes : current controversies concerning the freedom of religion and the freedom of expression before the European Court of Human Rights / Malcolm Evans -- Building a consensus on'national security' in Britain : terrorism, human rights and'core values' : the Labour Government (a retrospective examination) / Derek McGhee -- Terror, reason and rights / Eric Metcalfe -- Part III. Religious Dimensions -- Religiously rooted engagement in the relationship between human rights and security : a socio-anthropological approach / Charlotte Alfred -- The elimination of mutilation and torture in rabbinic thought and practice : a Jewish comment amidst the civil liberties, national security debate / David Novak -- Narrating religious insecurity : Islamic-Western conceptions of mutual threat / Abdelwahab El-Affendi -- Security and the state : a Christian realist perspective on the world since 9/11 / Robin Lovin.
Includes bibliographical references and index.
Keywords: National security -- Law and legislation; Terrorism -- Prevention -- Law and legislation; Terrorism (International law); Civil rights